Open Ankle Arthrodesis: a Systematic Review of Approaches and Fixation Methods. Issue 3 (April 2021) - van den Heuvel, Stein B.M.; Doorgakant, Ashtin; Birnie, Merel F.N.; Blundell, Chris M.; Schepers, Tim
Highlights: This study demonstrates an overall union rate of 95.5% in recent literature. Most used techniques in ankle arthrodesis are the anterior approach and screw-fixation. No significant differences were found between different techniques in ankle arthrodesis. Abstract: Background: Open ankle arthrodesis (OAA) remains the most widely used operation in end-stage ankle osteoarthritis. However, there is a large variation in terms of approach and fixation methods. The aim of this systematic review was to assess the effect of different approaches and fixation methods on the union rate, complication rate and functional outcome in OAA. Methods: A search of the online databases PubMed, Embase, and Cochrane library was performed to identify patients who underwent OAA with screw- and/or plate-fixation. Results: We identified 38 studies, including 1250 patients (1290 ankles). The union rate was 98% (95% CI 0.95–0.99) for the anterior, 96% (95% CI 0.92–0.98) for the lateral and 96% (95% CI 0.68–1.00) for the combined medial/lateral approach. Screw-fixation achieved an overall union rate of 96% (95% CI 0.93–0.98) and plate-fixation 99% (95% CI 0.96–0.99). The overall complication rate was 14%, 16% and 31% for the anterior, lateral and combined medial/lateral approaches respectively. It stood at 18% for screw-fixation and 9% for plate-fixation. The infection rate was 4%, 6% and 8% for the anterior, lateral and combined approaches respectively. Screw-fixation had an infection rate of 6% and plate-fixation 3%. The postoperative AOFAS scores were 76.8, 76.5 and 67.6 for the anterior, lateral and combined approaches respectively and 74.9 for screw- compared to 78.5 for plate-fixation. These differences did not reach statistical significance. Conclusion: This study, the first of its kind, found little difference in terms of results between approach and fixation method used in OAA. LEVEL OF EVIDENCE: Level IIa.